Pengembangan modul matematika berbasis pendekatan kontekstual pada materi kubus dan balok kelas VIII Sekolah Menengah Pertama (SMP) - Sutri, Dinila; Isharyadi, Ratri; Annajmi (Jurnal Pendidik Indonesia, 2023)
This research aims to produce a contextual approach-based mathematics module on cubes and rectangular prisms for 8th-grade junior high school students. The type of research used is Research and Development (R&D) with a modified 4-D research model into 3-D, namely Analysis, Design, and Development. The instruments used in this research are validation and practicality questionnaires. The results of the development of mathematics learning modules have been validated by three validators, with the overall average assessment aspects such as didactic aspects, content, language, and appearance reaching 3.60 with a criterion of very valid. Furthermore, the practicality of the modules is assessed based on trial and evaluation using teacher response questionnaires, with the average practicality score of the contextual-based mathematics module reaching 94% and the student response questionnaire reaching 84.25%, both categorized as very practical. Therefore, this mathematics learning module has been proven to be very valid and highly practical.